Predation on recent Marine and Fresh-Water Ostracod populations of The Central Region of The Republic Argentina - Kihn, Romina Gisela (2015)
The presence of evidence of depredation in ostracods valves from marine and freshwater environments of the central region of the republic Argentina are studied in this paper. In samples from intertidal environment (Puerto Rosales) a total of 800 shells of ostracods were recovered of which only 0.50% (4 valves) presented evidence of predation. In freshwater environments (Laguna Don Tomás) a total of 1447 valves were recovered of which only 1.10% (16 valves) presented evidence of predation. Two types of depredation fossil traces were determined: Oichnus simplex Bromley and Oichnus paraboloides Bromley. Oichnus simplex Bromley predominate over drilling Oichnus paraboloids Bromley attributed to predatory gastropods activity, both marine and continental environments. There was not relationship between the borehole diameter and the size of the predated valves. The ornamentation of the valves is not a character that conditions predation, since the species predated have different type of ornamentation from thin ribs to crosslinks with very prominent ribs.